Incidence of Deep Vein Thrombosis and Pulmonary Embolism in the Elective Pediatric Orthopaedic Patient. Issue 1 (January 2016) - Georgopoulos, Gaia; Hotchkiss, Mark S.; McNair, Bryan; Siparsky, Georgette; Carry, Patrick M.; Miller, Nancy H.
Abstract : Background: Although venous thromboembolism (VTE) has been well studied in the pediatric trauma population, rates of VTE associated with elective pediatric orthopaedic procedures have not been addressed in current literature. The purpose of this retrospective study was to identify the incidence of VTE in the elective pediatric orthopaedic surgical population and delineate subsets of this population at greatest risk. This study may provide valuable data to begin the process of resolving the controversy surrounding deep vein thrombosis prophylaxis in the pediatric orthopaedic population. Methods: The Pediatric Health Information System was queried for patients admitted on an ambulatory or inpatient basis, aged below 18 years, from January 2006 to March 2011 during which an elective orthopaedic surgery was the principal procedure performed. Patients with diagnoses or procedures related to infection, trauma, malignancy, or coagulopathies were excluded. Patients admitted through the emergency department or whose orthopaedic procedure was not performed on the admission date were excluded. Age, sex, ethnicity, race, admission year, and all procedures/diagnoses were recorded. The presence of VTE at the index admission or any subsequent readmission within 90 days was recorded. All criteria were coded using ICD-9-CM codes. Generalized logistic regression analyses were used to identify factors related to VTE. Results: A total of 143, 808 admissions (117, 676 patients) matched the inclusion criteria. Thirty-three had a VTE during the index admission with an additional 41 at subsequent readmissions, for a total incidence of 0.0515% by admission and 0.0629% by patient. In the multivariable model, variables significantly ( P <0.05) related to VTE included increasing age, admission type, diagnosis of metabolic conditions, obesity, and/or syndromes, and complications of implanted devices and/or surgical procedures. No procedure variables were significantly related to VTE in the multivariable model. Conclusions: The incidence of VTE in this cohort of pediatric patients undergoing elective orthopaedic surgery was 0.0515%. In children, underlying diagnosis seems to be a stronger predictor of VTE than procedures performed. Diagnosis with a metabolic condition, syndrome, and/or obesity, complications of implanted devices and/or surgical procedures, older age, and admission as an inpatient were significantly related to the development of a VTE. Level of Evidence: Level II—retrospective prognostic study.